2014
DOI: 10.1167/14.13.19
|View full text |Cite
|
Sign up to set email alerts
|

Compensation for red-green contrast loss in anomalous trichromats

Abstract: For anomalous trichromats, threshold contrasts for color differences captured by the L and M cones and their anomalous analogs are much higher than for normal trichromats. The greater spectral overlap of the cone sensitivities reduces chromatic contrast both at and above threshold. But above threshold, adaptively nonlinear processing might compensate for the chromatically impoverished photoreceptor inputs. Ratios of sensitivity for threshold variations and for color appearance along the two cardinal axes of Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 41 publications
6
39
0
Order By: Relevance
“…This is consistent with the reduced peak-to-trough reduction in chromatic difference signals at the input described in Sect. 1 and in agreement with the findings of Boehm et al [21] with respect to chromatic discrimination loss in anomalous observers. Nevertheless, when expressed as cone contrasts using average cone fundamentals for normal and anomalous observers, the values converged for all three classes of observers.…”
Section: Mpcsupporting
confidence: 92%
See 2 more Smart Citations
“…This is consistent with the reduced peak-to-trough reduction in chromatic difference signals at the input described in Sect. 1 and in agreement with the findings of Boehm et al [21] with respect to chromatic discrimination loss in anomalous observers. Nevertheless, when expressed as cone contrasts using average cone fundamentals for normal and anomalous observers, the values converged for all three classes of observers.…”
Section: Mpcsupporting
confidence: 92%
“…At high contrasts the curves flatten out, indicating that contrast discrimination should become worse, perhaps even showing saturating behavior as in rod discrimination at high luminance levels [41]. These results support MacLeod's prediction of response in the presence of output noise and Boehm et al's conclusions of a post-receptoral gain amplification [21].…”
Section: Contrast Appearance Along the L-m Axissupporting
confidence: 82%
See 1 more Smart Citation
“…Their longer-wave cones have very similar spectral sensitivities and thus the differences they convey are much weaker. Yet many seem to experience stronger color percepts than their reduced sensitivity predicts (Neitz et al, 2002, Regan and Mollon, 1997, Boehm et al, 2014). Again this could occur if post-receptoral mechanisms amplify their gain to match the weakened inputs.…”
Section: Adaptation and Compensationmentioning
confidence: 99%
“…Moreover, a recent study that explored the mechanism of color naming ability in red-green dichromats suggested that color naming ability is supported by residual activity in red-green opponent mechanism, as well as by blue-yellow and achromatic mechanisms (Moreira et al, 2014). As for anomalous trichromats, it has been found that red-green color appearance differs from normal vision, but it is recovered to a large degree by postreceptoral processing that compensates for the anomalous photopigment (Boehm, MacLeod & Bosten, 2014). …”
Section: Introductionmentioning
confidence: 99%